The Effect of Capital Adequacy Ratio (CAR) And Loan To Deposit Ratio (LDR) To Return On Asset (ROA) on PT BJB Tbk - Weny Juniarti (Yayasan Pendidikan Penelitian dan Pengabdian Al-amsi, 2021)
This study determines how the effect of Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Return On Assets (ROA) at PT. Bank BJB Tbk. This study uses data from the company's financial statements at PT. Bank BJB Tbk from 2011 to 2020. The data were processed and analyzed using the Eviews 9 application program. The results of the study showed that the Capital Adequacy Ratio (CAR) variable had no positive and insignificant effect on profitability which was calculated using return on assets (ROA). The Loan to Deposit Ratio (LDR) variable has no positive and insignificant effect on profitability which is calculated using return on assets (ROA). Capital Adequacy Ratio (CAR) and Loan To Deposit Ratio (LDR) have no significant effect on profitability which is calculated using Return On Assets (ROA) the results of R2 = 0.329 or 32.9% and the remaining 67.1% is influenced by other factors.